2019
DOI: 10.1108/jadee-06-2018-0068
|View full text |Cite
|
Sign up to set email alerts
|

Understanding causes of volatility in onion prices in India

Abstract: Purpose Post-2008 global food crisis the prices of perishable high-value food commodities, such as vegetables and fruits, in India have risen faster and become more volatile compared to that of cereals. The welfare consequences of price shocks though are well understood yet the policy responses to manage these remain blurred because of a lack of clarity on their causes. Focusing on onions that comprise an important constituent of the Indian diet, the purpose of this paper is to explore causes of high price vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
1
14
0
2
Order By: Relevance
“…In the Australian grains and oilseeds sectors, O'Donnell et al (2007) found that processors exercise monopoly and oligopsony toward consumers and producers. The study of Birthal et al (2019) concluded that the downstream market power of onion production is one of the major factors causing high price volatility in the onion market in India Yusuf and Trondsen (2014),. on the other hand, revealed that market power, in forms of access barriers, weakened competition in the Indonesian crab industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the Australian grains and oilseeds sectors, O'Donnell et al (2007) found that processors exercise monopoly and oligopsony toward consumers and producers. The study of Birthal et al (2019) concluded that the downstream market power of onion production is one of the major factors causing high price volatility in the onion market in India Yusuf and Trondsen (2014),. on the other hand, revealed that market power, in forms of access barriers, weakened competition in the Indonesian crab industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the domestic market level, some of the price setting factors include the timing of harvest, market distance and volume of sales (Yan et al, 2017). In an investigation of the causes of food price volatility, Birthal et al (2019) found production shocks, seasonality in production and market arrivals, internal trade, export policies and intermediaries market power as factors responsible for volatility of onion prices in India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, making food affordable is an important issue for such regions. Looking at general food commodities, Birthal et al (2019) argue that volatility in onion prices in India can have the effect of reduced consumption among the poor. Similarly, in Bangladesh, it was found that increasing commodity prices led smallholder households to reduce consumption of “high food value-enriched non-cereal” food items (Mottaleb and Rahut, 2018).…”
Section: Brief Review Of the Literaturementioning
confidence: 99%